A Comprehensive Review on Sameer Pannaga Rasa: An Ayurvedic Formulation - Loveshikha; Kapil, Pradeep; Gehlot, Abhishek; Sharma, O P (International Research Journal of Ayurveda & Yoga, 2024)
Sameer Pannaga Rasa mentioned in various classics is one of the Herbo mineral or Mineral drug formulations. Three varieties of this formulation are found in the Ayurveda texts with different ingredients, different Bhavana dravya and different method of preparation. The market available Sameer Pannaga Rasa is of Ayurvedic Formulary of India and its basic reference is taken from Ayurvediya Aushadhi Guna Dharma Shastra text. These three varieties are different from each other in context like Anupana, Bhavana dravya, duration for Bhavana, Dose, and Indications etc. Here an attempt has been made to comprehensive review through compilation of Sameer Pannaga Rasa mentioned in various classics and discuss about the properties of the ingredients, different method of preparation and detailed description about the commonly used method of preparation for the Sameer Pannaga Rasa which is Kupipakwa method.